Ijen Educative Geotourism: Mountain Trip Experience with Inclusive Design Approach - Jeremy Lovendianto; Ima Defiana (Center for Scientific Publication, 2023)
Ijen Geopark has geotourism prospects from its geosites, biosites and culture-sites diversities. This study aims to give concepts to design an educational geotourism facility that is accessible for diffable people with inclusive design approach. Design process uses force-based framework. Identified forces are accessibility, black lava rocks, site contour, and local materiality. Design method uses regionalism that responds to site and enhances regional characteristics. Tourists get the education through multi-sensory experiences. Circulation bridge is less than 8% incline for independent use by all users, with landing areas as viewpoints. Local bamboo plant stimulates auditory sense. Black lava rocks’ texture is recognized through tactile sensory.